Preparation method of novel conductive composite grounding material
By copolymerizing the conductive polymer with thermoplastic polyurethane and polyimide, and covering it on the galvanized steel wire core for thermal extension and iodine vapor treatment, the grounding material has been solved in a complex soil environment without stable conductivity and poor corrosion resistance in complex soil environments. and the problem of insufficient mechanical properties, high conductivity, high mechanical properties and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202510077023.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-02-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing grounding materials have problems such as unstable conductivity, poor corrosion resistance and insufficient mechanical properties in complex soil environments, especially during thunderstorms.
Conductive polymers are used to copolymerize with thermoplastic polyurethane and polyimide to form conductive polymer materials, and are coated on the galvanized steel wire core through extrusion process, and thermal extension and iodine vapor treatment are carried out to improve the conductivity and resistance of the material. Corrosion and mechanical properties.
It achieves high conductivity, high mechanical properties and corrosion resistance, improves the conductive stability and durability of grounding materials, and can work effectively in complex soil environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grounding materials, and in particular to a method for preparing a novel conductive composite grounding material. Background Art
[0002] Grounding is a protective measure taken to ensure the safety of power, communication, microelectronic equipment and other equipment, and to prevent short-circuit current from endangering the safety of people and equipment. It plays a role in discharging and equalizing lightning, static electricity and fault current. The grounding system is a concealed project, so the conductor buried in the earth's soil is connected to the relevant facilities, and the additional harmful current generated by the electrical equipment or other related devices during operation is introduced into the earth for dissipation; buildings, subways, petrochemical facilities, transmission line towers, substations, power plants, etc. all need to be grounded, and the grounding network is spread all over the underground. In order to achieve a benign electrical connection between the zero potential point of various electrical equipment and the earth, the zero potential parts of various electrical equipment are connected to the metal grounding body, and the good conduction between the metal grounding body and the earth is used to achieve the system requirements of working grounding, protective grounding, lightning protection, etc. The difference in the structure of the shell soil must ensure that the metal grounding body is well electrically connected to various soils (especially soils with high resistivity). Its design requirements are equivalent to the life of the surrounding facilities, generally ≥30 years. The soil structure is complex, and it is composed of gas, liquid and solid phases to form a multi-phase system. The soil contains water, air and various soluble salts, which act as electrolytes and have a corrosive effect on the metals serving in it. The corrosion form is mainly electrochemical corrosion. Since the soil is a multiphase system composed of gas, liquid and solid, the medium has poor fluidity, and the soluble salts, water content, oxygen content and porosity in different parts of the soil vary greatly. The soil properties are uneven, which leads to potential differences between different parts of the metal parts serving in it, especially in thunderstorm season. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a novel conductive composite grounding material to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a novel conductive composite grounding material, comprising the following preparation steps: (1) mixing a conductive polymer and a thermoplastic polyurethane in a mass ratio of 1:1.5-2.5, and extruding and granulating the mixture to obtain an intermediate A; (2) mixing the conductive polymer and the polyimide in a mass ratio of 1:1.5 to 2.5, and extruding and granulating to obtain an intermediate B; (3) Mixing intermediate A, intermediate B, molybdenum disulfide, aluminate coupling agent F-1, zedoaria flavonoids, melamine, and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline, heating to 150-230° C., copolymerizing for 10-20 hours, and extruding and granulating to obtain a conductive polymer material; (4) The conductive polymer material is coated on a wire core made of galvanized steel through an extrusion process, and is thermally stretched during the heating process. The wire core is then placed in iodine vapor for 10 to 20 hours to obtain a new conductive composite grounding material.
[0005] Furthermore, the process parameters of the extrusion granulation in step (1) are: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 125-160° C., and shear rate of 80-150 rpm.
[0006] Furthermore, the thermoplastic polyurethane in step (1) is BASF 685A.
[0007] Furthermore, the conductive polymer in step (1) and step (2) is composed of a 1.5 wt% silver acetate aqueous solution and bis(ethylene disulfide)tetrathiafulvene in a mass ratio of 1:1 to 8.
[0008] Furthermore, the molecular weight of the polyimide in step (2) is 30,000.
[0009] Furthermore, the process parameters of the extrusion granulation in step (2) are: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 265-300° C., and shear rate of 80-150 rpm.
[0010] Furthermore, the process parameters of the extrusion granulation in step (3) are: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 230-265° C., and shear rate of 80-150 rpm.
[0011] Furthermore, in step (3), the mass ratio of the intermediate A, the intermediate B, molybdenum disulfide, the aluminate coupling agent F-1, zedoaria flavonoids, melamine, and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline is 10:8~13:0.3~1:0.1~0.5:0.06~0.2:0.2~0.4:0.1~0.5.
[0012] Furthermore, the temperature of the extrusion process in step (4) is 260-300°C.
[0013] Furthermore, the thermal stretching ratio in step (4) is 1.1 to 1.3 times.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: The grounding material of the invention is prepared by mixing a conductive polymer into a thermoplastic polyurethane and a polyimide substrate and coating the conductive polymer on the outside of a metal rod core to achieve the effects of high conductivity, high mechanical properties and corrosion resistance.
[0015] First, silver acetate is used as a silver source and copolymerized with bis(ethylene disulfide)tetrathiafulvalene to form a conductive polymer, so that silver ions combine with tetrathiafulvalene in bis(ethylene disulfide)tetrathiafulvalene to increase the channel for charge transfer, thereby greatly improving the conductivity of the matrix. Next, they are mixed in thermoplastic polyurethane and polyimide substrates respectively, and then the two are copolymerized to obtain a conductive polymer material, thereby achieving corrosion resistance. The hard segments of polyurethane and polyimide are entangled with each other to form a hard segment domain, and with the increase of polyimide content, the rigidity of the hard segment chain is further enhanced, making it more difficult to destroy the ordered structure of the hard segment, thereby improving the mechanical properties of the matrix and enhancing the stability of conductivity.
[0016] Secondly, the conductive polymer material is coated on the outside of the metal rod core. Under the action of high-temperature curing, silver acetate is reduced to spherical nanosilver ions, which can provide anode protection, enhance the corrosion resistance of the matrix, and produce catalytic and oxidative degradation effects on the surrounding polyimide, so that the silver particles can contact each other to form a network of conductive paths. At the same time, the restriction of the polyurethane macromolecular chain segments prevents the further agglomeration of the silver particles and ensures their uniform dispersion, thereby improving the conductive stability of the grounding material. Then, gaseous iodine is introduced to transform the bis(ethylene disulfide)tetrathifulvene unit from the original neutral state to the cationic free radical state, and as the free iodine leaves, the conductivity of the matrix gradually increases. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the novel conductive composite grounding material prepared in the following examples are as follows: Conductivity: Take the embodiment and comparative example of the same size and measure their resistivity according to GB / T21698.
[0019] Corrosion resistance: The same size of the embodiment and the comparative example were taken and buried in alkaline soil for accelerated corrosion test. The soil temperature was 60°C, the water content was 20%, the total salt content was 18%, the pH was 9.5, and the time was 1000h. Then the resistivity was tested.
[0020] Mechanical properties: The same size of the embodiment and the comparative example were taken and their tensile strength was tested according to GB / T228.1.
[0021] Example 1; (1) A 1.5 wt% aqueous solution of silver acetate and bis(ethylene disulfide)tetrathiafulvene were mixed in a mass ratio of 1:1 to obtain a conductive polymer; a conductive polymer and BASF 685A were mixed in a mass ratio of 1:1.5, and extrusion granulation was performed, wherein the process parameters were: a screw diameter of 20 mm, an aspect ratio of 25:1, an extrusion temperature of 125°C, and a shear rate of 80 rpm to obtain an intermediate A; (2) A conductive polymer and a polyimide having a molecular weight of 30,000 were mixed in a mass ratio of 1:1.5 and extruded into granules. The process parameters were as follows: a screw diameter of 20 mm, an aspect ratio of 25:1, an extrusion temperature of 265°C, and a shear rate of 80 rpm to obtain an intermediate B; (3) Intermediate A, intermediate B, molybdenum disulfide, aluminate coupling agent F-1, zedoaria flavonoids, melamine, and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline are mixed, heated to 150°C, copolymerized for 10 hours, and extruded into granules. The process parameters are as follows: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 230°C, and shear rate of 80 rpm to obtain a conductive polymer material; the mass ratio of intermediate A, intermediate B, molybdenum disulfide, aluminate coupling agent F-1, zedoaria flavonoids, melamine, and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline is 10:8:0.3:0.1:0.06:0.2:0.1; (4) The conductive polymer material is extruded at a temperature of 260°C to be coated on a wire core made of galvanized steel. During the heating process, it is thermally stretched by 1.1 times and then allowed to stand in iodine vapor for 10 hours to obtain a new conductive composite grounding material.
[0022] Example 2; (1) A 1.5 wt% aqueous solution of silver acetate and bis(ethylene disulfide)tetrathiafulvene were mixed in a mass ratio of 1:5 to obtain a conductive polymer; a conductive polymer and BASF 685A were mixed in a mass ratio of 1:2 and extruded into granules, wherein the process parameters were as follows: a screw diameter of 20 mm, an aspect ratio of 25:1, an extrusion temperature of 140°C, and a shear rate of 120 rpm to obtain an intermediate A; (2) A conductive polymer and a polyimide having a molecular weight of 30,000 were mixed in a mass ratio of 1:2 and extruded into granules. The process parameters were as follows: a screw diameter of 20 mm, an aspect ratio of 25:1, an extrusion temperature of 285°C, and a shear rate of 120 rpm to obtain an intermediate B; (3) Intermediate A, intermediate B, molybdenum disulfide, aluminate coupling agent F-1, zedoaria flavonoids, melamine, and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline are mixed, heated to 190°C, copolymerized for 18 hours, and extruded into granules. The process parameters are as follows: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 245°C, and shear rate of 120 rpm to obtain a conductive polymer material. The mass ratio of intermediate A, intermediate B, molybdenum disulfide, aluminate coupling agent F-1, zedoaria flavonoids, melamine, and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline is 10:11:0.6:0.3:0.12:0.3:0.4. (4) The conductive polymer material is extruded at a temperature of 280°C to be coated on a wire core made of galvanized steel. During the heating process, it is thermally stretched by 1.2 times and then allowed to stand in iodine vapor for 15 hours to obtain a new conductive composite grounding material.
[0023] Example 3; (1) A 1.5 wt% aqueous solution of silver acetate and bis(ethylene disulfide)tetrathiafulvene were mixed in a mass ratio of 1:8 to obtain a conductive polymer; a conductive polymer and BASF 685A were mixed in a mass ratio of 1:2.5 and extruded into granules, wherein the process parameters were as follows: a screw diameter of 20 mm, an aspect ratio of 25:1, an extrusion temperature of 160°C, and a shear rate of 150 rpm to obtain an intermediate A; (2) A conductive polymer and a polyimide having a molecular weight of 30,000 were mixed in a mass ratio of 1:2.5 and extruded into granules. The process parameters were as follows: a screw diameter of 20 mm, an aspect ratio of 25:1, an extrusion temperature of 300°C, and a shear rate of 150 rpm to obtain an intermediate B; (3) Intermediate A, intermediate B, molybdenum disulfide, aluminate coupling agent F-1, zedoaria flavonoids, melamine, and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline are mixed, heated to 230°C, copolymerized for 20 hours, and extruded into granules. The process parameters are as follows: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 265°C, and shear rate of 150 rpm to obtain a conductive polymer material; the mass ratio of intermediate A, intermediate B, molybdenum disulfide, aluminate coupling agent F-1, zedoaria flavonoids, melamine, and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline is 10:13:1:0.5:0.2:0.4:0.5; (4) The conductive polymer material is extruded at a temperature of 300°C to be coated on a wire core made of galvanized steel. During the heating process, it is thermally stretched by 1.3 times and then allowed to stand in iodine vapor for 20 hours to obtain a new conductive composite grounding material.
[0024] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) and step (2) are different. Step (1) is changed to: bis(ethylene disulfide)tetrathiafulvene and BASF 685A are mixed in a mass ratio of 1:2, and extrusion granulation is performed. The process parameters are: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 140°C, and shear rate of 120 rpm to obtain intermediate A. Step (2) was modified as follows: bis(ethylene disulfide)tetrathifulvene and polyimide with a molecular weight of 30,000 were mixed in a mass ratio of 1:2, and extrusion granulation was performed. The process parameters were as follows: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 285° C., and shear rate of 120 rpm, to obtain intermediate B. The remaining steps were the same as those in Example 2.
[0025] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (4) is different. Step (4) is changed to: the conductive polymer material is extruded at a temperature of 280°C to be coated on a wire core made of galvanized steel, and during the heating process, it is thermally stretched at a stretching multiple of 1.2 times to obtain a new conductive composite grounding material; the remaining steps are the same as Example 2.
[0026] Effect example Table 1 below shows the performance analysis results of the novel conductive composite grounding materials of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2.
[0027] Table 1
[0028] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention uses silver acetate as a silver source, copolymerizes with bis(ethylene disulfide)tetrathifulvene to form a conductive polymer, increases the channel for charge transfer, and thus greatly improves the conductivity of the matrix. Then, it is mixed in a thermoplastic polyurethane and a polyimide substrate respectively, and then the two are copolymerized to obtain a conductive polymer material, thereby achieving corrosion resistance. The hard segments of the polyurethane and the polyimide are entangled with each other to form a hard segment phase domain, and as the content of the polyimide increases, the rigidity of the hard segment chain is further enhanced, making it more difficult to destroy the ordered structure of the hard segment, thereby improving the mechanical properties of the matrix and enhancing the stability of the conductivity. Finally, it is coated on the outside of the metal rod core. Under the action of high-temperature curing, silver acetate is reduced to spherical nanosilver ions, which can provide anodic protection, enhance the corrosion resistance of the substrate, and catalyze and oxidize the surrounding polyimide, so that the silver particles can contact each other to form a network of conductive paths. At the same time, the restriction of the polyurethane macromolecular chain segments prevents the further agglomeration of the silver particles and ensures their uniform dispersion, thereby improving the conductive stability of the grounding material. Then, gaseous iodine is introduced to transform the bis(ethylene disulfide)tetrathifulvene unit from the original neutral state to the cationic free radical state. As the free iodine leaves, the conductivity of the material gradually increases.
[0029] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a novel conductive composite grounding material, characterized in that: The method comprises the following preparation steps: (1) mixing a conductive polymer and a thermoplastic polyurethane in a mass ratio of 1:1.5-2.5, and extruding and granulating the mixture to obtain an intermediate A; (2) mixing the conductive polymer and the polyimide in a mass ratio of 1:1.5 to 2.5, and extruding and granulating to obtain an intermediate B; (3) Mixing intermediate A, intermediate B, molybdenum disulfide, aluminate coupling agent F-1, zedoaria flavonoids, melamine, and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline, heating to 150-230° C., copolymerizing for 10-20 hours, and extruding and granulating to obtain a conductive polymer material; (4) The conductive polymer material is coated on a wire core made of galvanized steel through an extrusion process, and is thermally stretched during the heating process. The wire core is then placed in iodine vapor for 10 to 20 hours to obtain a new conductive composite grounding material.
2. The method for preparing a novel conductive composite grounding material according to claim 1, characterized in that: The process parameters of the extrusion granulation in step (1) are as follows: the screw diameter is 20 mm, the aspect ratio is 25:1, the extrusion temperature is 125-160° C., and the shear rate is 80-150 rpm.
3. The method for preparing a novel conductive composite grounding material according to claim 1, characterized in that: The thermoplastic polyurethane in step (1) is BASF 685A.
4. The method for preparing a novel conductive composite grounding material according to claim 1, characterized in that: The conductive polymer in step (1) and step (2) is composed of a 1.5wt% silver acetate aqueous solution and bis(ethylene disulfide)tetrathiafulvene in a mass ratio of 1:1 to 8.
5. The method for preparing a novel conductive composite grounding material according to claim 1, characterized in that: The molecular weight of the polyimide in step (2) is 30,000.
6. The method for preparing a novel conductive composite grounding material according to claim 1, characterized in that: The process parameters of the extrusion granulation in step (2) are: screw diameter of 20 mm, aspect ratio of 25:1, extrusion temperature of 265-300° C., and shear rate of 80-150 rpm.
7. The method for preparing a novel conductive composite grounding material according to claim 1, characterized in that: The process parameters of the extrusion granulation in step (3) are as follows: the screw diameter is 20 mm, the aspect ratio is 25:1, the extrusion temperature is 230-265° C., and the shear rate is 80-150 rpm.
8. The method for preparing a novel conductive composite grounding material according to claim 1, characterized in that: The mass ratio of the intermediate A, intermediate B, molybdenum disulfide, aluminate coupling agent F-1, zedoaria flavonoids, melamine, and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline in step (3) is 10:8~13:0.3~1:0.1~0.5:0.06~0.2:0.2~0.4:0.1~0.
5.
9. The method for preparing a novel conductive composite grounding material according to claim 1, characterized in that: The temperature of the extrusion process in step (4) is 260~300℃.
10. The method for preparing a novel conductive composite grounding material according to claim 1, characterized in that: The thermal stretching multiple in step (4) is 1.1 to 1.3 times.
Citation Information
Patent Citations
Method of obtaining patterns in an organic conductor substrate and organic material thus obtained
CN101317281A
Method for preparing tetrathiafulvalene molecule-based micrometre and / or nano functional material
CN101497426A
Corrosion-resistant conductive polymer composite material as well as preparation method and application thereof
CN115536958A
Temperature-resistant conductive polymer composite material as well as preparation method and application thereof
CN116144163A
Conductive polymer composite material, preparation method thereof and grounding electrode comprising conductive polymer composite material
CN117153453A